ANALISIS TEOLOGIS MENGENAI BERIBADAH DI RUMAH DI TENGAH PANDEMI COVID-19 DI INDONESIA - Alexander Stevanus Luhukay (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2020)
Case COVID-19 (coronavirus) has become a global pandemic in Indonesia. To break the virus's spread, the government and church leaders carry out a social distancing process by encouraging church members to worship in their homes. This suggestion raises the pros and cons of the congregation. Most of the congregations have a dilemma about it. It is unusual worship, for they always do worship in church. Therefore, they need a theological answer as to whether worshipping at home is acceptable. This research aims to answer that dilemma by exploring the concept of worship in the Bible. The method used is hermeneutic with a textual and historical critique approach. As a result, worship at home does not reduce the essence of worship itself because the meaning of true worship is human life itself before God (Rom 12: 1-2). It should answer the pros and cons among congregation members about worship at home during the coronavirus pandemic